Bioinformatics Considerations and Approaches for High-Density Linkage Mapping in Aquaculture - Yun Li; Shikai Liu; RuijiaWang; Zhenkui Qin; Zhanjiang Liu (John Wiley & Sons Ltd., 2025)
Construction of genetic linkage maps is essential for genetic and genomic studies. As such, linkage maps have been constructed for a number of aquaculture species. Recent advances in sequencing and genotyping technologies have made it possible to generate high-density and high-resolution genetic linkage maps. However, the use of large numbers of molecular markers have also brought greater challenges for linkage analysis. In this chapter, we provide a practical introduction to genetic linkage mapping, and describe map construction procedures using large numbers of markers. Our experience and lessons learned should be helpful for those who are facing similar challenges. Genetics as a branch of science has a relative short history of less than 160 years. It started in the mid-1800s, when Gregor Johann Mendel conducted a series of experiments with the inheritance of a number of traits in peas. Through observations of phenotypes and analysis of the distribution of phenotypes among individuals in different generations, Mendel established his groundbreaking principles of inheritance, the so-called Mendel’s laws, which included the lawof segregation (the “First Law”), the law of independent assortment (the “Second Law”), and the law of dominance (the “Third Law”). The law of segregation states that, during gamete formation, the alleles for each gene segregate fromeach other, so that each gamete carries only one allele for each gene; the law of independent assortment states that genes for different traits segregate independently during the formation of gametes; and the law of dominance states that some alleles are dominant, while others are recessive, and that recessive alleles are masked by dominant alleles (Bateson &Mendel, 1909; Miko, 2008).These principles of inheritance set the foundation for genetics. However, considering what is known today as genetic linkage, it can be inferred that Mendel was only partially correct, since genes next to each other, because of their linkage, most often do not segregate independently.